Comparisons of synchronous measurement methods on various moduli of asphalt mixtures. (15th January 2018) - Lv, Songtao; Liu, Chaochao; Yao, Hui; Zheng, Jianlong
Graphical abstract: Highlights: Two synchronous measurement methods of different moduli for asphalt mixture were proposed. The effectiveness of two synchronous measurement methods was verified. The correlation and difference of moduli obtained by four test methods were analyzed. Abstract: Two new test methods were proposed to measure the different moduli of asphalt mixtures simultaneously based on four-point bending and indirect tensile tests. The new calculating formulas were derived for tensile and compressive moduli of asphalt mixtures under four-point bending loading model, which combining the equilibrium condition and the plane hypothesis in elastic mechanics theory. Meanwhile, on the basis of the test principle of indirect tensile moduli and Hooke's law in two-dimensional stress states, the new calculating formulas were derived in indirect tensile loading model. The moduli tests of four-point bending, indirect tensile, direct tension and unconfined compression were carried out separately to verify effectiveness of the new methods. The results of tensile and compressive moduli from the two new methods were compared with the direct tension moduli tests and unconfined compression moduli tests. The correlations among them were analyzed. The result indicates that the tensile and compression moduli of asphalt mixtures show a significant difference, and can be obtained by two methods simultaneously. The two new methods realize the synchronous measuring of various moduli of asphalt mixtures.